An exploration of interactive metadiscourse markers in academic research article abstracts in two disciplines. (June 2013) - Khedri, Mohsen; Heng, Chan Swee; Ebrahimi, Seyed Foad
A generic analysis of research article abstracts can cover issues of different types; among them are linguistic features. An integral part of linguistic features of research article abstracts is interactive metadiscourse usage that can assist to make the text persuasive and unfolding to a discourse community. The main principle behind applying interactive metadiscourse is the view of writing as socially engaging; specifically, it indicates the ways writers project themselves into their arguments to declare their attitudes and commitments to the readers. This study aimed to explore how interactive metadiscourse markers are deployed by research article abstract writers belonging to different disciplinary communities within the soft sciences, while trying to reach the audience by creating a well-organized discourse. Hyland's (2005) interpersonal model of metadiscourse was adopted to analyze 60 research article abstracts written in Applied Linguistics and Economics. Based on the results, there were marked variations found across the two disciplines in terms of interactive metadiscourse markers.